INFLUENCE OF FINANCIAL PRUDENCE ON THE PERFORMANCE OF THE INSURANCE INDUSTRY IN KENYA - Ajwang, Benard Onyango; Karanja Ngugi, P.; Ogollah, Kennedy; Orwa, Dr. George (IJRDO - Journal of Business Management, 2016)
The measure of performance of insurance companies must not be just on their rate of return on investment but should also include aspects that relates to financial prudence like levels of customer satisfaction, speed of claims settlement and also quality of underwriting services. Financial Strategic Intelligence is the key and road map to be followed by any insurance company that aspires to succeed in the undefined industry climate. It was however found that there are marked differences in the conformity and usage of strategic intelligence and its components in the insurance industry with a measurable difference between large and small organisations. It is, however, generally viewed that the use of a strategic intelligence framework could greatly enhance decision-making.